Manajemen Pengelolaan Kantin Sehat SD Muhammadiyah 22 Surakarta - Nisa*, Choirun; Faradila, Divia; Rohayati, Fadhilah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This article aims to identify the management of a healthy canteen at SD Muhammadiyah 22 Surakarta. The research method used in this study is a qualitative descriptive method. The data used is primary data which comes from observations, interviews, and filling out questionnaires. In this study, researchers used data collection techniques in the form of observation, interviews, and filling out questionnaires. To analyze the research data used descriptive analysis techniques. The results of this study indicate that: 1) the planning of a healthy canteen at SD Muhammadiyah 22 Surakarta starts from identifying service needs to determining the canteen schedule; 2) the organization of a healthy canteen at SD Muhammadiyah 22 Surakarta is carried out by establishing a canteen organizational structure along with its duties and responsibilities; 3) the implementation of a healthy canteen at SD Muhammadiyah 22 Surakarta is run by the school together with canteen guards; and 4) supervision of the healthy canteen at SD Muhammadiyah 22 Surakarta using internal supervision and external supervision from the local health center.